2019
DOI: 10.1021/acs.est.8b04838
|View full text |Cite
|
Sign up to set email alerts
|

Motility of Shewanella oneidensis MR-1 Allows for Nitrate Reduction in the Toxic Region of a Ciprofloxacin Concentration Gradient in a Microfluidic Reactor

Abstract: Subsurface environments often contain mixtures of contaminants in which the microbial degradation of one pollutant may be inhibited by the toxicity of another. Agricultural settings exemplify these complex environments, where antimicrobial leachates may inhibit nitrate bioreduction, and are the motivation to address this fundamental ecological response. In this study, a microfluidic reactor was fabricated to create diffusioncontrolled concentration gradients of nitrate and ciprofloxacin under anoxic conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Since each MGC-extracted culture contained different subpopulations, we expected growth on plates of only those that adapted to at least the corresponding ciprofloxacin concentration. We note that in recent work, we measured the MIC of cells using several different methods (e.g., plating, liquid culture) with comparable results …”
Section: Methodssupporting
confidence: 52%
“…Since each MGC-extracted culture contained different subpopulations, we expected growth on plates of only those that adapted to at least the corresponding ciprofloxacin concentration. We note that in recent work, we measured the MIC of cells using several different methods (e.g., plating, liquid culture) with comparable results …”
Section: Methodssupporting
confidence: 52%
“…In these settings, cell wall surfaces, extracellular polymeric substances and other organic molecules produced and influenced by microbial metabolism can act as direct surface control on the rate and composition of crystalline mineral growth (6). In situ kinetic experiments in Yellowstone National Park carbonate hot springs have demonstrated that the physical cell presence and biomolecules produced by living microorganisms can more than double mineral precipitation rates compared to when they are absent (32). These direct catalytic influences (protein catalysis) (33) can now be linked to microbial gene targets identified by future microscopy-to-omics analyses in kidney stones.…”
Section: Biomineralization In Human Kidneys and Natural And Man-made mentioning
confidence: 99%
“…Compared to traditional physicochemical treatments, like physisorption, biological reduction, and ion exchange, electrochemical reduction of nitrate has received more and more attention due to its characteristics such as simple operation, environment friendliness, and low cost. , The electrochemical nitrate reduction reaction (ENRR) is a complex reaction involving many intermediates . More importantly, the first step of electrochemically reducing nitrates to nitrites is the rate-determining step for the overall ENRR. , Thus, it is necessary to develop efficient cathodes for improving the rate of nitrate reduction.…”
Section: Introductionmentioning
confidence: 99%